The Role Of Advocates In The Legal Protection Of Children Accused Of Committing Narcotics Crimes Based On Law Number 11 Of 2012 Concerning The Criminal Justice System For Children - Kaban, Sukma Yertina; Hasibuan, Lidya Rahmadhani; Nasution, Chairuni (JURNAL HUKUM SEHASEN, 2026)
Advocates play a crucial role as legal defenders, particularly in upholding children's rights, from the investigation stage to court decisions. This study aims to analyze the role of advocates in the legal assistance process for children accused of drug offenses and to examine the implementation of the principles of legal protection for children as stipulated in Law Number 11 of 2012. The handling of cases involving child drug offenders must prioritize diversion as a means of resolving the case outside the criminal justice process to avoid the negative impacts of detention and harsh sentences. The legal protection provided by advocates extends beyond defense in court, but also includes assistance during the investigation, prosecution, and trial to ensure the best interests of the child. The research method used is a normative juridical approach, examining laws and case studies. The results indicate that advocates' responsibilities extend beyond formal defense to children, including legal education, ensuring fair legal proceedings, and promoting restorative justice as mandated by the Children's Juvenile Justice Law. However, in practice, challenges remain, including a lack of understanding among advocates regarding child protection approaches and a limited availability of advocates with specialized competencies in child advocacy. Therefore, ongoing training and supporting regulations are needed to strengthen the role of advocates in realizing a just and humane juvenile criminal justice system.